In situ monitoring of isophorone diisocyanate-based flexible polyurethane foams formation. (January 2018) - Eceiza, I; Irusta, L; Barrio, A; Fernández-Berridi, MJ
Novel isophorone diisocyanate-based flexible polyurethane foams were prepared by the one-step method in a computerized foam qualification system (FOAMAT). The experimental conditions to obtain this type of foams, in relation to the nature and concentration of catalysts as well as the reaction temperature, were established as no data were available in scientific literature. The chemical reactions occurring during the foam generation process were monitored in situ by attenuated total reflectance-FTIR spectroscopy. The kinetics of the foam generation was fitted to an n th order model and the data showed that the foaming process adjusted to a first-order kinetics. The physical changes as pressure, foam height, and dielectric polarization were monitored by the FOAM software (FOAMAT). According to these parameters, the foaming process was divided into four steps: bubble growth, bubble packing, cell opening, and final curing.